Cultivating Religious Character through School Culture - Retnasari, Lisa; Hakim, Arini Prihartini; Hermawan, Hendra; Prasetyo, Danang (International Journal of Educational Qualitative Quantitative Research, 2023)
The foundation of manners and the factors determining character development are crucial for education. School culture is one way to cultivate moral qualities that assist the progress of character education. This study aims to describe and identify the supporting and inhibiting factors for implementing religious character education through school culture. This type of research is descriptive research using a qualitative approach. The object of this research is the whole process of implementing religious character planting through school culture. This research was conducted at SD Muhammadiyah Wirobrajan II Yogyakarta, Indonesia. The results of this study show that instilling religious character through school culture is carried out in three stages: planning, implementation, and evaluation. The supporting factors of religious character include religious programs, facilities, and infrastructure that have been fulfilled. The inhibiting factors for the implementation of religious character cultivation include environmental conditions. The contribution of this study provides information about supporting and inhibiting factors for the implementation of religious character education through school culture.